2018
DOI: 10.5334/labphon.65
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of information structure, semantics, prosody, and word ordering in Spanish intransitives

Abstract: A production experiment was run to examine how information structure and verbal semantics affect word ordering and nuclear stress placement in intransitive sentences in Venezuelan Spanish. Unaccusative verbs in Spanish are said to be more likely to be subject final (VS order) than unergative verbs, while in languages like English, this is marked with stress shift (i.e., Sv, caps show the nuclear stress). It has long been contended, however, that the semantic factors underlying split intransitivity actually aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…Oral production studies have corroborated these findings, showing that speakers are able to prosodically augment an element in narrow focus even when it occurs non-finally. Such findings have been found across various dialects, including Mexican Spanish (Kim 2016), Venezuelan Spanish (Calhoun et al 2018), Castilian Spanish (Vanrell Bosch & Soriano 2013 and Argentinean Spanish (Gabriel 2010).…”
Section: Na Placement In Spanishmentioning
confidence: 80%
See 3 more Smart Citations
“…Oral production studies have corroborated these findings, showing that speakers are able to prosodically augment an element in narrow focus even when it occurs non-finally. Such findings have been found across various dialects, including Mexican Spanish (Kim 2016), Venezuelan Spanish (Calhoun et al 2018), Castilian Spanish (Vanrell Bosch & Soriano 2013 and Argentinean Spanish (Gabriel 2010).…”
Section: Na Placement In Spanishmentioning
confidence: 80%
“…While much of the experimental research on narrow focus in Spanish has contradicted previous theoretical approaches about lack of prosodic plasticity in Spanish, less experimental work has been conducted to examine NA placement in broad focus contexts. One exception is Calhoun et al (2018), who conducted an oral production task to test the effects of verb type (unaccusative versus unergative) and information status on word order and NA placement in Venezuelan Spanish intransitives. This study found that SV order occurred more frequently in Spanish intransitives than predicted.…”
Section: Na Placement In Spanishmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been noted (e.g. Calhoun at al. 2018;Schwarz 2010) that crosslinguistically presentational constructions are prosodically and syntactically marked.…”
Section: Theoretical Prerequisitesmentioning
confidence: 85%